Innovation in Islamic Education Learning through the Utilization of Digital Library at the Riyadlotul Mujahidin Islamic Institute Ngabar Ponorogo - Ratna Utami Nur Ajizah; Fahmi Aulia Zaki Romdhoni; Annisaa Auliya Firdaus (Yayasan Dinamika Ilmu Banyuwangi, 2025)
Innovation in education continues to evolve alongside technological advancements, including in the learning of Islamic Religious Education. This research aims to explore the utilization of digital libraries as an innovative tool in the learning of Islamic Education at the Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo. Digital libraries, as technology-based educational resources, offer broad access to relevant and up-to-date learning materials. This research employs a qualitative approach with a case study method to analyze how digital libraries are implemented in the learning process at the institution. Data were collected through observations, interviews with lecturers and students, as well as document analysis related to the use of the digital library. The research results show that digital libraries have improved the accessibility and quality of learning materials, accelerated the learning process, and encouraged active student engagement in Islamic Education studies. Although there are challenges related to training and technology adaptation, the benefits gained, such as easier access to information and better interactivity, are very significant. This research recommends further development of digital library facilities and ongoing training for lecturer and students to maximize the potential of technology in religious education. This finding is expected to serve as a reference for other religious educational institutions in adopting digital technology to enhance the quality of learning.